(untitled) (International Journal of Food and Nutritional Sciences, 2022)
SAQ, plyometric training, and strength training all have a major impact on athletic performance. SAQ, plyometric training, and strength training, or any combination of these three types of training, may improve soccer players’ motor skills and performance, according to previous study. The aim of this study was to look at how the participants’ lower bodies responded to eight weeks of strength training and a mix of SAQ and plyometric exercise. The findings of this study showed that after 8 weeks of training, the group that received strength training had significantly improved lower body performance compared to the groups who received SAQ and Plyometric training and the control group.